Adenoma and Polyp Detection Rates in Colonoscopy according to Indication - Erika S. Boroff; Molly Disbrow; Michael D. Crowell; Francisco C. Ramirez (Gastroenterology Research and Practice)
Background. Adenoma detection rate (ADR) is a validated quality measure for screening colonoscopy, but there are little data for other indications. The distribution of adenomas is not well described for these indications. Aim. To describe ADR and the adenoma distribution in the proximal and distal colon based on colonoscopy indication. Methods. Outpatient colonoscopies are subdivided by indication. PDR and ADR for the entire colon and for proximal and distal colon. Data were compared using generalized estimating equations to adjust for clustering amongst endoscopists while controlling for patient age and gender. Results. 3436 colonoscopies were reviewed (51.2%: men (n=1759)). Indications are screening 49.2%, surveillance 29.3%, change in bowel habit 8.4%, bleeding 5.8%, colitides 3.0%, pain 2.8%, and miscellaneous 1.5%. Overall ADR was 37% proximal ADR 28%, and distal ADR 17%. PDR and ADR were significantly higher in surveillance than in screening (PDR: 69% versus 51%; ADR: 50% versus 33%; p=0.0001). Adenomas were more often detected in the proximal than in the distal colon, for all indications. Conclusions. Prevalence of polyps and adenomas differs based on colonoscopy indication. Adenoma detection is highest in surveillance and more commonly detected in the proximal colon. For quality assurance, distinct ADR and PDR targets may need to be established for different colonoscopy indications.